Decylubiquinone Inhibits Colorectal Cancer Growth Through Upregulating Sirtuin2 - Li, Jinlian; Zheng, Shuting; Cheng, Ting; Li, Yuanyuan; Mai, Xiaobin; Jiang, Guangchun; Yang, Yongxia; Zhang, Qianqian; Li, Jiangchao; Zheng, Lingyun; Wang, Lijing; Qi, Cuiling (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is one of the leading causes of cancer-related death worldwide. Decylubiquinone (DUb), a coenzyme Q10 analog, was reported to inhibit breast cancer growth and metastasis by us. However, the influence of DUb on CRC remains unclear. Herein, we found that DUb significantly inhibited CRC growth in the patient-derived xenograft (PDX) and CT26 xenograft models. DUb was further identified to significantly suppress CRC cell proliferation, colony formation, migration and invasion in a dose-dependent manner, while not inhibiting CRC cell apoptosis from flow cytometry assay. Sirtuin2 (SIRT2), a member of the sirtuin protein family, plays a critical role in growth and metastasis in various cancers. Moreover, DUb inhibited CRC progression by upregulating SIRT2. These findings reveal that DUb has the potential to a novel drug for the treatment of CRC by inhibiting CRC cell proliferation.